Green Tax Reform for SDG 13 - Anugrah, Surya; Sudiati, Rochma; Puspa, Eka Septariana; Suyono, Windy Permata; Hermawan, Sabo (School of Accountancy, University of Agung Podomoro, 2025)
Climate change poses a critical threat to global sustainability, requiring immediate and coordinated policy responses. As part of Sustainable Development Goal 13 (SDG 13), which urges urgent action to combat climate change and its impacts, fiscal instruments such as carbon taxes have emerged as vital tools. This study explores the role of green tax reform—particularly carbon taxation—in supporting the achievement of SDG 13. By analyzing the effectiveness of carbon tax policies in various developing countries, the study highlights how optimized tax systems can both reduce greenhouse gas emissions and generate sustainable public revenues. It also investigates the institutional and economic challenges that hinder effective implementation, especially in emerging economies. The findings suggest that transparent policy design, gradual implementation, and integration with broader environmental and fiscal strategies are key to maximizing the impact of green taxes. This research contributes to the discourse on environmental fiscal reform and offers recommendations for policymakers aiming to align tax systems with climate goals.